COVID-NURSE: evaluation of a fundamental nursing care protocol compared with care as usual on experience of care for noninvasively ventilated patients in hospital with the SARS-CoV-2 virus—protocol for a cluster randomised controlled trial. Issue 5 (26th May 2021) - Richards, David A; Sugg, Holly VR; Cockcroft, Emma; Cooper, Joanne; Cruickshank, Susanne; Doris, Faye; Hulme, Claire; Logan, Phillipa; Iles-Smith, Heather; Melendez-Torres, G.J; Rafferty, Anne Marie; Reed, Nigel; et al.
Abstract : Introduction: Patient experience of nursing care is correlated with safety, clinical effectiveness, care quality, treatment outcomes and service use. Effective nursing care includes actions to develop nurse–patient relationships and deliver physical and psychosocial care to patients. The high risk of transmission of the SARS-CoV-2 virus compromises nursing care. No evidence-based nursing guidelines exist for patients infected with SARS-CoV-2, leading to potential variations in patient experience, outcomes, quality and costs. Methods and analysis: we aim to recruit 840 in-patient participants treated for infection with the SARS-CoV-2 virus from 14 UK hospitals, to a cluster randomised controlled trial, with embedded process and economic evaluations, of care as usual and a fundamental nursing care protocol addressing specific areas of physical, relational and psychosocial nursing care where potential variation may occur, compared with care as usual. Our coprimary outcomes are patient-reported experience (Quality from the Patients' Perspective; Relational Aspects of Care Questionnaire); secondary outcomes include care quality (pressure injuries, falls, medication errors); functional ability (Barthell Index); treatment outcomes (WHO Clinical Progression Scale); depression Patient Health Questionnaire-2 (PHQ-2), anxiety General Anxiety Disorder-2 (GAD-2), health utility (EQ5D) and nurse-reported outcomes (Measure of Moral Distress for Health Care Professionals). For our primary analysis, we will use a standard generalised linear mixed-effect model adjusting for ethnicity of the patient sample and research intensity at cluster level. We will also undertake a planned subgroup analysis to compare the impact of patient-level ethnicity on our primary and secondary outcomes and will undertake process and economic evaluations. Ethics and dissemination: Research governance and ethical approvals are from the UK National Health Service Health Research Authority Research Ethics Service. Dissemination will be open access through peer-reviewed scientific journals, study website, press and online media, including free online training materials on the Open University's FutureLearn web platform. Trial registration number: ISRCTN13177364; Pre-results .